Survey of the frequency of USH1 gene mutations in a cohort of Usher patients shows the importance of cadherin 23 and protocadherin 15 genes and establishes a detection rate of above 90%. Issue 9 (5th May 2006) - Roux, A-F; Faugère, V; Le Guédard, S; Pallares-Ruiz, N; Vielle, A; Chambert, S; Marlin, S; Hamel, C; Gilbert, B; Malcolm, S; Claustres, M
Abstract : Background: Usher syndrome, a devastating recessive disorder which combines hearing loss with retinitis pigmentosa, is clinically and genetically heterogeneous. Usher syndrome type 1 (USH1) is the most severe form, characterised by profound congenital hearing loss and vestibular dysfunction. Objective: To describe an efficient protocol which has identified the mutated gene in more than 90% of a cohort of patients currently living in France. Results: The five genes currently known to cause USH1 ( MYO7A, USH1C, CDH23, PCDH15, and USH1G ) were tested for. Disease causing mutations were identified in 31 of the 34 families referred: 17 in MYO7A, 6 in CDH23, 6 in PCDH15, and 2 in USH1C . As mutations in genes other than myosin VIIA form nearly 50% of the total, this shows that a comprehensive approach to sequencing is required. Twenty nine of the 46 identified mutations were novel. In view of the complexity of the genes involved, and to minimise sequencing, a protocol for efficient testing of samples was developed. This includes a preliminary linkage and haplotype analysis to indicate which genes to target. It proved very useful and demonstrated consanguinity in several unsuspected cases. In contrast to CDH23 and PCDH15, where most of the changes are truncating mutations, myosin VIIA has both nonsense and missense mutations. Methods for deciding whether a missense mutation is pathogenic are discussed. Conclusions: Diagnostic testing for USH1 is feasible with a high rate of detection and can be made more efficient by selecting a candidate gene by preliminary linkage and haplotype analysis.